2007
DOI: 10.1111/j.1440-1754.2007.01149.x
|View full text |Cite
|
Sign up to set email alerts
|

Arterial thromboembolic disease: A single‐centre case series study

Abstract: Arterial TE occurred as frequently as venous TE in our tertiary paediatric population. The clinical outcome and long term sequelae of such events are significant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 34 publications
0
29
0
1
Order By: Relevance
“…7,27 Mortality after pulmonary embolism is as high as 20%. 28 In a study of 98 pediatric patients, Monagle et al 29 demonstrated that direct arterial thrombosis-related mortality was 4% in infants and 9% in children in a study of 98 pediatric patients. Outcomes of arterial strokes and cerebral sinovenous thrombosis are poor, with high mortality, and up to two thirds of patients have resulting permanent neurological damage.…”
Section: Serious Complications Of Thrombosis and Surgical Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…7,27 Mortality after pulmonary embolism is as high as 20%. 28 In a study of 98 pediatric patients, Monagle et al 29 demonstrated that direct arterial thrombosis-related mortality was 4% in infants and 9% in children in a study of 98 pediatric patients. Outcomes of arterial strokes and cerebral sinovenous thrombosis are poor, with high mortality, and up to two thirds of patients have resulting permanent neurological damage.…”
Section: Serious Complications Of Thrombosis and Surgical Outcomesmentioning
confidence: 99%
“…Cerebral arterial thrombosis carries a high risk of cardioembolic stroke, but noncerebral arterial thrombosis also carries substantial risk of ischemic injury. 29 Occlusive and symptomatic thrombi were at higher risk of complications. Finally, thromboses found in vessels where there had been indwelling access lines were at lower risk of complications, which might reflect their localization in peripheral vessels farther from central blood circulation.…”
Section: Serious Complications Of Thrombosis and Surgical Outcomesmentioning
confidence: 99%
“…The few researches on the argument would seem to orient towards the surgical treatment as a first-line intervention, life-saving, even in case of infection of the atrial catheter. In fact only in one study it was reported a positive outcome in two patients treated with anticoagulant medical therapy [10]. Recent researches have also linked the increased incidence of thrombotic events with genetic disorders of coagulation [11], and therefore suggest to comprehensively study the coagulation factors of the patients to reduce the recurrency of those events [12].…”
Section: Discussionmentioning
confidence: 99%
“…Los niños mayores tienen más probabilidades de desarrollar tromboembolia en el sistema nervioso central. 10 Según el Registro Internacional Canadiense, el 89% de los casos de trombosis estuvieron asociados con la colocación de catéteres intravasculares. 11 Brus, et al 12 informaron que la formación de coágulos, la fibrinólisis y el sistema calicreína-cininas se activan simultáneamente en los recién nacidos prematuros con SDR grave, lo que resulta en alteraciones en la coagulación.…”
Section: Discussionunclassified